Katuk Leaves (Sauropus androgynus (L.) Merr) on Hemoglobin Level among Pregnant Women in Third Trimester - Masriyah, Memes Nur; Dahlan, Febry Mutiariami; Lail, Nurul Husnul (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: In 2018, 41,8% of amternal mortality in developing countries was caused by anemia in pregnancy, the prevalence of anemia in Indonesia is still very high at 44,2%. One of the causes of anemia is a lack of iron in the body. Anemia can be prevented by consuming foods that contain iron and vitamin C to help the absorbtion process, by consuming katuk leaves while continuing to consume Fe Tablets according to government recommendations.Purpose: This study aims to determine the effect of Katuk Leaves (Sauropus androgynus) and Fe Tablets on hemoglobin levels among pregnant women in third trimester.Methods: This research is aquassy experiment pre and post test with control group design. The population in this study was 86 third trimester pregnant women which 45 had anemia in last 6 month at Private Midwifery Practice N. The sample were divided by intervention group and cotrol group, each group was 15 pregnant women, according to sample theory of experimental research. The sampling technique used purposive sampling. The research instrument used observation sheets and Digital Hemoglobinometer. The data analyzed with parametric test, the t-test.Results: The result of statistic tests showed that there was an effect of katuk leaves  and Fe tablets on hemoglobin level with p value of 0,00 (<0,005).Conclusion: Consumption katuk leaves and Fe tablet is more effective in changing hemoglobin levels compared to consuming Fe tablets only.